Pengaruh Penerapan Model Pembelajaran Peta Konsep dengan Media Fotografi terhadap Hasil Belajar Siswa - Boedy Irhadtanto; Fruri Stevani; Ayis Crusma Fradani (IKIP PGRI Bojonegoro, 2022)
Abstract: This research aims to determine the effect of the concept map learning model with photographic media on economics learning outcomes on the subject of the Indonesian economy for class X students of SMA Muhammadiyah Sumberrejo Bojonegoro in the 2021/2022 academic year. This research is an experimental type of posttest-only control design with a quantitative approach. Statistical data analysis used was t test. After doing the research and obtaining the data, the data then to be analyzed where the tcount Value is 11.42 which is compared to the ttable value is 2.003 at the 5% significance level in the two-party test. Because the value of tcount is greater than the value of tcount (11.42 > 2.003), then H1 is accepted and H0 is rejected. From the results of this research, it can be concluded that the application of the concept map learning model with photographic media has a positive effect on economic learning outcomes on the subject of the Indonesian economy for class X students of SMA Muhammadiyah Sumberrejo Bojonegoro in the 2021/2022 academic year. Abstrak: Penelitian ini bertujuan untuk mengetahui pengaruh model pembelajaran peta konsep dengan media fotografi terhadap hasil belajar Ekonomi pada pokok bahasan perekonomian Indonesia siswa kelas X SMA Muhammadiyah Sumberrejo Bojonegoro tahun pelajaran 2021/2022. Penelitian ini merupakan eksperimen yang berjenis posttest-only control design dengan pendekatan kuantitatif. Analisis data statistik yang digunakan adalah uji t. Setelah dilakukan penelitian dan diperoleh data, data tersebut kemudian dianalisis dimana perolehan nilai thitung sebesar 11,42 yang dibandingkan dengan nilai ttabel sebesar 2,003 pada taraf signifikansi 5% dalam uji dua pihak. Karena nilai thitunglebih besar daripada nilai ttabel (11,42 > 2,003), maka H1 diterima dan H0 ditolak. Dari hasil penelitian tersebut dapat dikesimpulan bahwa penerapan model pembelajaran peta konsep dengan media fotografi berpengaruh positif terhadap hasil belajar Ekonomi pada pokok bahasan perekonomian Indonesia siswa kelas X SMA Muhammadiyah Sumberrejo Bojonegoro tahun pelajaran 2021/2022.